(3, -21)
5x+3+x=24 6x+3=24 6x=21 x=3.5
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.
x-3-7x=21 -6x=21+3 6x=-24 x=-4
3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3
(3, -21)
5x+3+x=24 6x+3=24 6x=21 x=3.5
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.
x-3-7x=21 -6x=21+3 6x=-24 x=-4
3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3
6x plus 3 equals to 8x plus 14 would lead to x = - 5.5.
y=(6x-5)/3
-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2
-6x+3 = -7-5x 7+3 = 6x-5x 10=x
9x + 3 - 6x - 2 = 3x + 1
6x + 2 = 6 6x = 4 x = 2/3
6x + 3 = 2x + 5 4x = 2 x=1/2